Salud integral y subjetividades de escolares sobre el consumo de psicotrópicos y variables psicosociales en un contexto social (2023)
ABSTRACT: Exploratory-descriptive research with a mixed approach. The techniques were used semi-structured and focus groups. Selection of a sample, N=75 Colombian students object study from grades 6 to 11, affected by violence during 2017 and 2018. The multivariate statistical analysis of the data applied Pearson’s Chi squared (Chi2P), P <0, 05 by cut groups, according to the psychosocial variables of communication, functioning and family vulnerability, depression, and suicide.The relevant results indicate a negative communication relationship in the family nucleus (44.4%), poor reading practice (30%) and daily study (34.7%), among others; and, the consumption of alcoholic beverages, marijuana, methamphetamine and poor mental health. This study reveals little understanding of the social realities impact that limit to forge integral permanent human development. This towards the transformation of a more humanistic progressive society that achieve challenges, such as: 1) Build and develop together other public policies that conceive psycho-didactic constructs from young age, and the schoolchildren understand the impact multidimensional of a critical problem of global public health. 2) Innovate the psycho-educational process to expand skills and abilities to young people that allow them to decide and prevent the consumption of psychotropics with more awareness. This study reveals little understanding of the social realities impact that limit to forge integral permanent human development. This towards the transformation of a more humanistic progressive society that achieve challenges, such as: 1) Build and develop together other public policies that conceive psycho-didactic constructs from young age, and the schoolchildren understand the impact multidimensional of a critical problem of global public health. 2) Innovate the psycho-educational process to expand skills and abilities to young people that allow them to decide and prevent the consumption of psychotropics with more awareness.